The Brunel Music Rating Inventory-2 is a reliable and valid instrument for older cardiac rehabilitation patients selecting music for exercise. (March 2016) - Clark, Imogen N.; Baker, Felicity A.; Peiris, Casey L.; Shoebridge, Georgie; Taylor, Nicholas F.
Music with motivating qualities might support exercise adherence in older adults with cardiac disease. The Brunel Music Rating Inventory-2 (BMRI-2), a 6-item scale with motivational quotients ranging from 6 to 42 developed to facilitate music selection for exercise, has been validated with young adults. However, the suitability of the BMRI-2 for older adults is unknown. We tested reliability (internal consistency, test-retest reliability, and measurement error) and validity (content and construct) of the BMRI-2 with older adults in cardiac rehabilitation. Eleven men and 9 women (M age = 71.6 years, SD = 8.9) selected two pieces of music and used the BMRI-2 to rate the motivational quality of these for a walking task. BMRI-2 ratings demonstrated high internal consistency. Test-retest reliability and levels of measurement error were acceptable. Content was evaluated as relevant and comprehensive. There was convergence with flow scales, and discrimination between music selections with differing motivational quotients ( p < .01). The BMRI-2 demonstrates acceptable psychometric properties for older adult cardiac rehabilitation patients.